Victims of commemoration : the architecture and violence of confronting the past in Turkey - Çaylı, Eray (Contemporary issues in the Middle East., 2022)
"Victims of Commemoration studies activist and official commemorations held at three sites of historical violence in Turkey, architectural projects for turning them into memorial museums, and the reverberations of these commemorative acts and artifacts across the everyday life of the city where each site is located"--